ภูมิปัญญาท้องถิ่นของการรักษาโรคแบบพื้นบ้านในจังหวัดพิษณุโลก - กาญจนศิริ วิเรขา (Community and Social Development Journal, 2016)
The objectives of the research were 1) to study acknowledgement and collection, knowledge management of folk wisdom about some villagers medicinal herbs in Phitsanulok province 2) to study knowledge transfer of folk wisdom about some villagers medicinal herbs in Phitsanulok province. The samples were 16 villagers using folk medicinal herbs in Phitsanulok province by purposing sampling. There were 16 persons inhabited in Maung District (37.50%). The others inhabited in Wangthong, Prompiram, Bangrakam, Bangkratum and Nakornthai District. Qualied structural interview form was the research tool (IOC = 0.67-1). The results found that the folk wisdom was the folk treatment with medicinal herbs, for instance, abdominal pain, abdominal distension, carminative, coating peptic ulcer, toothache, cough, sore throat, allergy, dizziness, dysmenorrhea, skin diseases, itching rash on arm and neck, conjunctivitis, hyperlipidemia, fatty liver disease, diabetes, miltitus myalgia, leg pain and bruises. Acknowledgement and collection of this folk wisdom was mainly conveyed and remembered from villagers philosopher (75.00%). At least was from reading textbook and self-studying (6.25%). This knowledge management by memory it wasnt record in textbook. The main medicinal herb knowledge transfer by treatment demonstration and self-recognition (68.75%) and was not transfer of any (6.25%).